A cross-disciplinary research framework at institution level and beyond - Apostolos Argyris; Emilio Hernández-García; Maxi San Miguel (Nature Communications)
Rethinking and restructuring cross-disciplinary research requires innovative models and the Institute for Cross-Disciplinary Physics and Complex Systems (IFISC) stands as a powerful example. Since its creation, IFISC has grown fourfold, now hosting 90 researchers from 15 different countries. Its unique structure fosters collaborations and a shared sense of belonging, built on a common foundation in complex systems. By bridging diverse disciplines and providing cutting-edge training, IFISC is shaping the next generation of researchers while offering a blueprint for how to reorganize research resources to foster cross-disciplinary research at institution levels and beyond.